Affinity purified anti-citrullinated protein/peptide antibodies target antigens expressed in the rheumatoid joint - Ossipova, Elena; Cerqueira, Catia Fernandes; Reed, Evan; Kharlamova, Nastya; Israelsson, Lena; Holmdahl, Rikard; Nandakumar, Kutty Selva; Engstrom, Marianne; Harre, Ulrike; Schett, Georg; Catrina, Anca I.; Malmstrom, Vivianne; et al. (Arthritis Research & Therapy, 2014)
A major subset of patients with rheumatoid arthritis (RA) is characterized by the presence of circulating autoantibodies directed to citrullinated proteins/peptides (ACPAs). These autoantibodies, which are commonly detected by using an enzyme-linked immunosorbent assay (ELISA) based on synthetic cyclic citrullinated peptides (CCPs), predict clinical onset and a destructive disease course. In the present study, we have used plasma and synovial fluids from patients with RA, for the affinity purification and characterization of anti-CCP2 reactive antibodies, with an aim to generate molecular tools that can be used in vitro and in vivo for future investigations into the pathobiology of the ACPA response. Specifically, this study aims to demonstrate that the surrogate marker CCP2 can capture ACPAs that bind to autoantigens expressed in vivo in the major inflammatory lesions of RA (that is, in the rheumatoid joint).Plasma (n = 16) and synovial fluid (n = 26) samples were collected from RA patients with anti-CCP2 IgG levels of above 300 AU/mL. Total IgG was isolated on Protein G columns and subsequently applied to CCP2 affinity columns. Purified anti-CCP2 IgG was analyzed for reactivity and specificity by using the CCPlus® ELISA, in-house peptide ELISAs, Western blot, and immunohisto-/immunocytochemistry.Approximately 2% of the total IgG pool in both plasma and synovial fluid was CCP2-reactive. Purified anti-CCP2 reactive antibodies from different patients showed differences in binding to CCP2 and differences in binding to citrullinated peptides from ?-enolase, vimentin, fibrinogen, and collagen type II, illustrating different ACPA fine-specificity profiles. Furthermore, the purified ACPA bound not only in vitro citrullinated proteins but, more importantly, in vivo-generated epitopes on synovial fluid cells and synovial tissues from patients with RA.We have isolated ACPAs from plasma and synovial fluid and demonstrated that the CCP2 peptides, frequently used in diagnostic ELISAs, de facto act as surrogate antigens for at least four different, well-characterized, largely non-cross-reactive, ACPA fine specificities. Moreover, we have determined the concentration and proportion of CCP2-reactive IgG molecules in rheumatoid plasma and synovial fluid, and we have shown that the purified ACPAs can be used to detect both in vitro- and in vivo-generated citrullinated epitopes by various techniques. We anticipate that these antibodies will provide us with new opportunities to investigate the potential pathogenic effects of human ACPAs.
EVALuna2:12981